2002
DOI: 10.5380/avs.v7i1.3971
|View full text |Cite
|
Sign up to set email alerts
|

Correlações Genéticas, Fenotípicas E De Ambiente Entre Os Pesos De Várias Idades Em Bovinos Da Raça Guzerá No Estado De São Paulo

Abstract: 4Professor Adjunto da UFMS -Campus de Três Lagoas, MS.RESUMO -Este trabalho tem como finalidade estudar as correlações genéticas, fenotípicas e de ambientes sobre os pesos de animais da raça Guzerá, criados no estado de São Paulo, aos 205 (P205), 365 (P365) e 550 (P550) dias de idade. Para realização das análises estatísticas, utilizouse da metodologia de modelos mistos, programa MTDFREML. O modelo estatístico continha os efeitos aleatórios de animal, touro, vaca e o erro; e, como efeitos fixos de grupo contem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
2
2
0
5
Order By: Relevance
“…Production traits had moderate to high positive genetic and phenotypic correlations between each other (Table 3) as expected. Malhado et al (2002) and Santos et al (2005) found high correlations between weights at 205 and 550 days of age (close to this work). These results show that intermediate weights have high correlations with subsequent weighings, indicating that animals may be selected early in life.…”
Section: Resultssupporting
confidence: 89%
“…Production traits had moderate to high positive genetic and phenotypic correlations between each other (Table 3) as expected. Malhado et al (2002) and Santos et al (2005) found high correlations between weights at 205 and 550 days of age (close to this work). These results show that intermediate weights have high correlations with subsequent weighings, indicating that animals may be selected early in life.…”
Section: Resultssupporting
confidence: 89%
“…This indicates that improvements in one trait will imply improvements of other traits. The estimates of the direct additive genetic correlations were stronger than 0.70 at most ages and are in accordance with other studies in Brazil [23], [24] and Africa [25], [26]. With these results, it is necessary to consider the risk of selecting for greater weights at any age [27] because the later the selection is performed the greater the response is for mature weight.…”
Section: Discussionsupporting
confidence: 89%
“…However, the correlation obtained for BW12 and BW18 (0.30 6 0.11) was lower than that found by Santos et al (2005) for the Nellore breed (0.97) and by Malhado et al (2002) and Mucari and Oliveira (2003) for the Guzerá breed (0.65 and 0.62, respectively). Nonetheless, the high environmental correlation (0.80 6 0.02) indicated that not only were these traits influenced by additive action of the same genes but also there was a non-additive and/or environmental genetic association.…”
Section: Discussionmentioning
confidence: 55%